Near hydration of singly charged monoatomic ions in extremely diluted solutions: the effect of temperature and pressure - Bulavin, Viktor Ivanovych; Vunik, Ivan Nikolajevych; Kramarenko, Andrii Viktorovych; Rusinov, Alexandr Ivanovych (Національний технічний університет "Харківський політехнічний інститут", 2021)
The diffusion coefficient 0iD and the distance of translational displacement of Li+, Na+K+, Cs+, Cl– and Br– ions d in water at 298.15 K –423.15 K (25 K step) and pressure from 0.0981 to 784.5 MPa (98.1 MPa step) were calculated from the literature data on limiting molar electrical conductivity. The 0iD values for these ions increase with pressure growth from 0.0981 to 98.1 MPa at 298.15 K. Further pressure increase (up to 785 MPa) leads to decrease in 0iD. Temperature growth under isobaric conditions leads to an increase in 0iD. Parameter (d – ri) (deviation from the Stokes–Einstein law, riis ion structural radius) was used as a criterion for the type of ion solvation. It is shown that Li+ and Na+ ions behave as cosmotropes, or positively solvated structure–forming ions having (d– ri) > 0. The Cs+, Cl–, Br– ions behave as chaotropes, or negatively solvated structure–breaking ions having (d– ri) < 0. For the K+ ion, the (d – ri) deviation is alternating. At 0.0981 MPa and 298.15 K, the K+ ion is a chaotrope. But at 320 K (Tlim) parameter (d – ri) = 0. It corresponds to the transition from negative to positive solvation. Above Tlimat P = const, the K+ ion is a cosmotrope. At 298.15 K and up to 98.1 MPa, the pressure causes the same change in the (d – ri) deviation as the temperature. On the contrary, at 320 K and higher, the pressure affects the near hydration in the direction opposite to the temperature.

Коефіцієнт дифузії 0iD та довжина дифузійного зміщення d іонів Li+, Na+K+, Cs+, Cl– and Br– у воді при 298,15 К – 423,15 К (шаг 25 К) і тиску від 0,0981 до 784,5 МПа (шаг 98,1 МПа) розраховані на підставі літературних даних щодо їх граничної молярної електричної провідності. Величини 0iD цих іонів зростають при 298,15 К зі збільшенням тиску від 0,0981 до 98,1 МПа. Подальше підвищення тиску до 785 МПа призводить до зменшення 0iD. Зростання температури в ізобаричних умовах призводить до збільшення 0iD. Параметр (d – ri) (відхилення від закону Стокса–Ейнштейна, ri-структурний радіус іона) використаний як критерій типу сольватації іонів. Показано, що іони Li+і Na + ведуть себе як космотропи, або позитивно сольватовані структуроутворюючі іони, для яких (d – ri) > 0. Іони Cs+, Cl– і Br– хаотропи, або негативно сольватовані структуро–руйнуючі іони для яких ( d– ri) < 0. Для іона K+ параметр (d– ri) є знакозмінним. При 0,0981 МПа та 298,15 К іон K+ – хаотроп, але при 320 K (Tгран) величина (d– ri) = 0. Це відповідає переходу від негативної до позитивної сольватації. Вище Tгран при P = const іон K+ є космотропом. При 298,15 К і до 98,1 МПа тиск спричиняє таку ж зміну (d– ri), як і температура. При 320 К і вище тиск впливає на ближню гідратацію у напрямку, протилежному дії температури.
Ближня гідратація однозарядних одноатомних іонів у гранично розбавлених розчинах: вплив температури та тиску
Keywords: diffusion displacement length; positive and negative solvation; довжина дифузійного зміщення; негативна сольватація